PWE-008 Colorectal cancer screening programs and the rate of surgical oncology procedures in the veneto region (italy). (17th June 2017) - Saia, M; Rosa-Rizzotto, E; Guido, E; Germanà, B; Monica, F; Caroli, D; Dupuis, A; Pilati, P; Lazzari, F De
Abstract : Introduction: Colorectal cancer (CRC) is a leading cause of cancer mortality in the Veneto Region (North-east Italy). Population screening of adults between 50 and 75 for CRC was begun in 2002, and it became standard practice in all 21 local health units (LHU) of the region in 2008, 14 LHU provided in the program also follow-up colonoscopy and 7 LHU no. This study was carried out to evaluate the impact on surgery rates of CRC screening and follow-up programs. Method: This is a retrospective cohort study on administrative data based on anonymous computerised database of Veneto Region hospital discharges between 2000 and 2015. All Veneto residents (in screening age) discharge records with principal diagnosis of CRC treated with surgery were included in the study. The number of patients studied rose approximately 18% reaching 1, 547, 097 for the last year (2015). The Standardised Hospitalisation Ratio (SHR) per five-year age group was calculated and expressed per 10 000 population. Results: During the study period, 30 399 surgical procedures for colorectal cancer were performed (colon 63%, rectum 36%, secondary malignant neoplasm 1%) with a SHR of 139.1, higher in males (OR: 1.66; CI 95%: 1.62–1.7; p<0.05). An analysis of the annual SHR distribution uncovered two distinct phases: during the first phase there was a rising tendency that reached a maximum value in 2007 (166, 9; X2 trend: 46.731; p<0.05) and during the second there was a falling tendency that reached its minimum value in 2015 (102.3; X2 trend: 429.791; p<0.05), with a total reduction of 28%. The cancer stratification by site shows that the rate of surgical procedures of the proximal colon during the last year was the same as the 2000 value (41.5), instead there was a significant decrease (−37, 3%; X2 trend: 559.282; p<0.05) in the rate of procedures on the distal colon and rectum which fell from 94.4 to 59.2 (Figure1). The stratification of LHU in which the screening program included a follow-up colonoscopy and others didn't show significant difference in the reduction in surgical procedures (Figure2). Conclusion: Study findings confirmed that CRC screening was effective in reducing the number of oncological surgical oncology procedures particularly with regard to the distal colon and rectum. Data analysis showed that the screening seemed to accelerate reaching the peak rate in surgical procedures that took place in 2007. After that time point the number of operations began to fall as far as the distal colon was concerned (it fell by 37.3%). Finally data suggest that the real benefit in reduction of oncological surgery procedures is due to the first screening colonoscopy. Disclosure of Interest: None Declared